2019
DOI: 10.1161/jaha.118.010860
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐Like Receptor 9 Plays a Pivotal Role in Angiotensin II–Induced Atherosclerosis

Abstract: Background Toll‐like receptor ( TLR ) 9 recognizes bacterial DNA , activating innate immunity, whereas it also provokes inflammation in response to fragmented DNA released from mammalian cells. We investigated whether TLR 9 contributes to the development of vascular inflammation and atherogenesis using apolipoprotein E–deficient ( Apoe −/− ) mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 45 publications
0
50
0
Order By: Relevance
“…Likewise, TLR7 and TLR9 appear to play protective roles because lipid aggregation, macrophage infiltration and accumulation, and production of pro-inflammatory cytokines are exacerbated in both Tlr7 −/− Apoe −/− and Tlr9 −/− Apoe −/− mice ( 52 , 53 , 54 ). In contrast, other groups have reported that TLR7 or TLR9 blockade may have beneficial effects in other murine atherosclerosis models by reducing scar tissue, lipid accumulation, macrophage infiltration, and plaque instability ( 55 , 56 , 57 ).…”
Section: Toll-like Receptorsmentioning
confidence: 86%
“…Likewise, TLR7 and TLR9 appear to play protective roles because lipid aggregation, macrophage infiltration and accumulation, and production of pro-inflammatory cytokines are exacerbated in both Tlr7 −/− Apoe −/− and Tlr9 −/− Apoe −/− mice ( 52 , 53 , 54 ). In contrast, other groups have reported that TLR7 or TLR9 blockade may have beneficial effects in other murine atherosclerosis models by reducing scar tissue, lipid accumulation, macrophage infiltration, and plaque instability ( 55 , 56 , 57 ).…”
Section: Toll-like Receptorsmentioning
confidence: 86%
“…The pivotal role of TLR9 has recently been reported in angiotensin II-induced atherosclerosis. 18 There was increased circulating levels of cfDNA in angiotensin IIinfused ApoE -/mice whereas TLR9 blockade could suppress the proinflammatory activation of macrophages and vascular inflammation. 61 In addition, the activation of TLR9 has been indicated by hepatocyte mtDNA in driving nonalcoholic steatohepatitis.…”
Section: Cytoplasmic Mtdna Induced By Ecv Extract Could Activate Tlr9mentioning
confidence: 97%
“…17 Recently, evidence has accumulated to indicate that TLR9 plays a pivotal role in the development of vascular inflammation through proinflammatory activation of macrophages in angiotensin II-induced atherosclerosis. 18 In addition, pharmacological blockade of TLR9 can attenuate atherosclerotic lesion formation, suggesting TLR9 may serve as a potential therapeutic target for atherosclerosis. 18 TLR9 also recognizes endogenous self-DNA termed damage-associated molecular patterns (DAMPS) from injured mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, TLR9 activates IRFs and/or NF-κB, which produces interferons and cytokines, leading to the acceleration of inflammatory responses in these diseases [ 2 , 36 38 ]. In addition, other studies demonstrated that TLR9 promotes p38 mitogen-activated protein kinase (MAPK) activation and the subsequent NF-κB activation, stimulating inflammation [ 19 , 55 ]. On the other hand, a few studies reported that ligation of TLR9 with its ligand has beneficial effects on some disease context such as cerebral ischemia/reperfusion injury by activation of PI3K/Akt signaling [ 56 ].…”
Section: Role Of Tlr9 In Inflammatory Diseasesmentioning
confidence: 99%